2022
DOI: 10.3390/molecules27103327
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Improves Antioxidant Capacity and Reduces Inflammation in the Lungs of Rats with Monocrotaline-Induced Pulmonary Hypertension

Abstract: Cannabidiol (CBD) is a plant-derived compound with antioxidant and anti-inflammatory properties. Pulmonary hypertension (PH) is still an incurable disease. CBD has been suggested to ameliorate monocrotaline (MCT)-induced PH, including reduction in right ventricular systolic pressure (RVSP), a vasorelaxant effect on pulmonary arteries and a decrease in the white blood cell count. The aim of our study was to investigate the effect of chronic administration of CBD (10 mg/kg daily for 21 days) on the parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Interestingly, the effects of CBD are quite different in different cell subpopulations involved in innate immunity. For example, CBD exerts a prevalent inhibitory effect on astrocytes [ 92 , 93 , 105 ] and PMN [ 26 , 36 , 94 , 153 , 155 , 156 , 157 , 158 , 159 , 160 , 164 ], whereas, in microglia, oligodendrocytes, monocytes/macrophages, and mast cells, results are contradictory, with some authors reporting anti-inflammatory effects for CBD [ 90 , 90 , 99 , 101 , 102 , 103 , 104 , 105 , 106 , 110 , 111 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 124 , 125 , 126 , 127 , 129 ] and other authors reporting proinflammatory effects [ 89 , 107 , 108 , 110 , 111 , 120 , 122 , 123 , 124 , 125 , 129 ]. Lastly, to the best of our knowledge, no studies have reported CBD’s effects on dendritic cells, NK cells, eosinophils, and basophils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the effects of CBD are quite different in different cell subpopulations involved in innate immunity. For example, CBD exerts a prevalent inhibitory effect on astrocytes [ 92 , 93 , 105 ] and PMN [ 26 , 36 , 94 , 153 , 155 , 156 , 157 , 158 , 159 , 160 , 164 ], whereas, in microglia, oligodendrocytes, monocytes/macrophages, and mast cells, results are contradictory, with some authors reporting anti-inflammatory effects for CBD [ 90 , 90 , 99 , 101 , 102 , 103 , 104 , 105 , 106 , 110 , 111 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 124 , 125 , 126 , 127 , 129 ] and other authors reporting proinflammatory effects [ 89 , 107 , 108 , 110 , 111 , 120 , 122 , 123 , 124 , 125 , 129 ]. Lastly, to the best of our knowledge, no studies have reported CBD’s effects on dendritic cells, NK cells, eosinophils, and basophils.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotaxis and tissue infiltration are fundamental processes in the inflammatory cascade; for this reason, CBD’s effects on these processes were studied by several authors. The reported results showed that CBD not only inhibits macrophages chemotaxis, as shown by Sacerdote in an in vitro model [ 88 ], but also tissue infiltration, as shown in different animal models of inflammatory diseases, such as liver inflammation [ 81 ], multiple sclerosis [ 87 ], pulmonary hypertension [ 92 ], and colitis [ 83 ].…”
Section: Effects Of Cbd On Immune Systemsmentioning
confidence: 99%
“…The antioxidant activity of CBD [ 32 ] as well as its combined regimens with other antioxidants [ 33 ] have drawn much attention recently The antioxidant and anti-inflammatory effects of CBD in monocrotaline-induced pulmonary hypertension have been reported [ 34 ]. CBD was found to be more effective than vitamin C and E as a neuroprotective antioxidant [ 35 ] Herein, H 2 CBD and Compound 4 presented similar antioxidant activity as VC, but exhibited a much higher thermostability of antioxidant activity than VC.…”
Section: Discussionmentioning
confidence: 99%
“…The naturally occurring cannabinoid CBD has been reported to possess robust anti‐inflammatory properties (Dos‐Santos‐Pereira et al, 2020; Henshaw et al, 2021) that are illustrated for instance in animal models of pulmonary hypertension (Krzyzewska et al, 2022), rheumatoid arthritis (Lowin et al, 2020), interstitial cystitis/bladder pain (Kuret et al, 2023) and brain degeneration (Dos Santos Pereira et al, 2020; Dos‐Santos‐Pereira et al, 2016; Meyer et al, 2022). Here, we wished to evaluate the anti‐inflammatory potential of two synthetic structural analogs of CBD, 4′‐F‐CBD (Breuer et al, 2016; Li et al, 2020) and HU‐910 (Horvath et al, 2012) using brain glial cells in culture.…”
Section: Discussionmentioning
confidence: 99%